Replay and representation dynamics in the hippocampus of freely flying bats - Angelo Forli; Wudi Fan; Kevin K. Qi; Michael M. Yartsev (Nature, 2025)
Abstract Cognitive functions for navigation and memory rely on emergent properties of neural ensembles in the hippocampus, such as activity replay1–5 and theta sequences6–9. However, whether and how these phenomena generalize across species with distinct navigational demands and neurophysiological properties remains unclear. Here we wirelessly recorded neural activity from large populations of cells and local field potentials from the hippocampus of freely flying Egyptian fruit bats (Rousettus aegyptiacus) engaged in free, spontaneous foraging behaviour. During rest, we identified time-compressed forward and reverse replays of multiple flight trajectories coinciding with sharp-wave ripples. Notably, replays occurred predominantly at locations that were both spatially and temporally distant from the replayed behaviour, and their speed scaled with trajectory length, challenging present models of replay mechanisms. During flight, neural ensembles exhibited fast representational sweeps, in which the decoded location moved ahead of the bat’s position cyclically. In contrast to reports in rodents, sweeps occurred in the absence of theta oscillations, and were instead phase locked to a prominent motor behavioural rhythm—the bat’s wing-beat cycle. This suggests that behaviourally relevant sensorimotor rhythms can interact with hippocampal ensemble dynamics in a highly structured manner. Combined, our findings challenge existing models of ensemble dynamics in the mammalian hippocampus, and highlight the importance of comparative studies in ethologically relevant conditions for elucidating brain function.